Coinfecção natural com o vírus da necrose hipodérmica e hematopoiética infecciosa (VNHHI) e o vírus da mionecrose infecciosa (VMI) em Litopenaeus vannamei no Nordeste do Brasil (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Cultivation of whiteleg shrimp (Litopenaeus vannamei) constitutes a growing aquaculture industry in Northeast Brazil. Similar to other animals that are intensively farmed, shrimp experience disease outbreaks, which are a constant threat and cause eventually significant economical losses. Infectious hypodermal and hematopoietic necrosis virus (IHHNV) and infectious myonecrosis virus (IMNV) are prevalent epizootic viral agents in Brazil. In a routine monitoring program for the diagnosis of IHHNV and IMNV, using molecular techniques like conventional PCR, reverse transcription coupled with PCR (RT-PCR) and absolute quantitative real time PCR (qPCR), we found that most positive samples of shrimp were simultaneously co-infected with both viruses. This survey is the first to show the occurrence of a natural co-infection that is caused by IHHNV and IMNV in penaeid shrimp attacked by viral disease that were cultivated in Northeast Brazil. Taken together, RTPCR can be readily employed in the routine diagnostic screening program for shrimp viruses in the aquaculture industry. Moreover, in combination with qPCR, diagnosis of the viral load and co-infection can be absolutely assessed and the data used to assist differential management plans for epizootic control.